Antecedents of Customer Citizenship Behavior in Local Coffee Shops - Jofira, Hilda; Sabur, Moch.; Fadhilah, Dylan Achmad (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This research aims to analyze the influence of price justice, procedural justice, customer trust, customer satisfaction, and customer loyalty on customer citizenship behavior. The sampling technique in this research used "purposive sampling," with the criteria for respondents being individuals who had purchased coffee at a local coffee shop. This research uses primary data obtained through questionnaires distributed to 245 respondents. Data were analyzed using the SEM method carried out by the AMOS program. The results of this research are: (1) Price Justice has a positive influence on Customer Trust, (2) Procedural Justice has a positive influence on Customer Trust, (3) Customer Trust has a positive influence on Customer Loyalty, (4) Customer Trust has a positive influence on Customer Satisfaction, (5) Customer Satisfaction has a positive effect on Customer Loyalty, (6) Customer Satisfaction has a positive effect on customer citizenship behavior, and (7) Customer Loyalty has a positive effect on customer citizenship behavior.